'Come Join the Rock Gharaana': The Cultural Politics of MTV's Kurkure Desi Beats Rock On. (March 2013) - Coventry, Chloe
In the first two decades of liberalization MTV has been a symbol of the complicated trajectory of transnational media in Indian public culture. A juggernaut cultural force and arguably one of the most potent dynamics in the globalization of youth culture, MTV, whose content in India is largely film-music oriented, has recently (2009 ) introduced a rock-centric 'making-the band' show called Kurkure Desi Beats Rock On (KDBRO) that taps into and draws from a six-decades old culture of rock music performance in urban middle-class India. Drawing from personal interviews and examining musical and discursive texts from KDBRO's first season, this article interprets how the show's producers and judges have attempted to ascertain an appropriately 'Indian' yet 'rock' sound, with musical outcomes that display tension between a desire for audible cultural nationalism and the practicalities of performing a transnational musical form. Through close reading of the show's musical and discursive negotiations I argue that the figure of the rock musician is a conduit for complicated cultural politics in which a mandate for cultural 'authenticity' is troubled by the realities of participation in a globalized media field—and that this dynamic speaks to larger social transformations in an economically globalized India.